If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5(x + -2) = -4 + 2x + -6 Reorder the terms: 3x + -5(-2 + x) = -4 + 2x + -6 3x + (-2 * -5 + x * -5) = -4 + 2x + -6 3x + (10 + -5x) = -4 + 2x + -6 Reorder the terms: 10 + 3x + -5x = -4 + 2x + -6 Combine like terms: 3x + -5x = -2x 10 + -2x = -4 + 2x + -6 Reorder the terms: 10 + -2x = -4 + -6 + 2x Combine like terms: -4 + -6 = -10 10 + -2x = -10 + 2x Solving 10 + -2x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + -2x + -2x = -10 + 2x + -2x Combine like terms: -2x + -2x = -4x 10 + -4x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 10 + -4x = -10 + 0 10 + -4x = -10 Add '-10' to each side of the equation. 10 + -10 + -4x = -10 + -10 Combine like terms: 10 + -10 = 0 0 + -4x = -10 + -10 -4x = -10 + -10 Combine like terms: -10 + -10 = -20 -4x = -20 Divide each side by '-4'. x = 5 Simplifying x = 5
| -297=-3+6(7-8n) | | -6+5(2-x)=4 | | 12=7+3x | | x+4=4x+7-3x | | 4(2-t)-(3-2t)=2 | | 9+4x=13+6x | | 6(b+8)=84 | | 2(3x-4)+10=5(x+14) | | 6x-6+9x-1=3x+12x-10 | | 4(8k+5)=84 | | 180d=3.6*108 | | 180d=3.6*120 | | 4(2x+3)-8=8x+4 | | 0.8w-0.5+0.2w=5 | | 180d=3.6*50 | | -9a-81=9(a+9) | | 5x=1-1y | | 5x+11x-6=4(4x+9) | | 3.6d=180*6 | | 2(x+4)=56 | | 3.6d=180*5 | | 5k+25=16 | | -8(4r-1)=-184 | | .75x+7=.25x-5 | | 16=r+(-1) | | 4847647363/3763747647373773=n | | 5(u+8)-7u=36 | | 8(8-6r)=112 | | 12(-3+-2x)(8+-1x)=0 | | 2m+15-3m=28 | | 2(x-8)+16-14x=62 | | 3.6d=180*4 |